MIMO capacity for deterministic channel models: sublinear growth. (30th May 2012) - Bentosela, François; Cornean, Horia D.; Marchetti, Nicola
<x xml:space="preserve">Abstract</x> This is the second paper by the authors in a series concerned with the development of a deterministic model for the transfer matrix of a MIMO system. In our previous paper, we started from the Maxwell equations and described the generic structure of such a deterministic transfer matrix. In the current paper, we apply those results in order to study the (Shannon‐Foschini) capacity behavior of a MIMO system as a function of the deterministic spread function of the environment and the number of transmitting and receiving antennas. The antennas are assumed to fill in a given fixed volume. Under some generic assumptions, we prove that the capacity grows much more slowly than linearly with the number of antennas. These results reinforce previous heuristic results obtained from statistical models of the transfer matrix, which also predict a sublinear behavior. Copyright © 2012 John Wiley & Sons, Ltd.